Five Novel RPGR Mutation in brief: Mutations in Families with XLinked Retinitis Pigmentosa - Guevara Fujita, María Luisa (2000)
X-linked forms of retinitis pigmentosa (XLRP) are among the most severe because of their early onset, often leading to significant visual impairment before the fourth decade. RP3, genetically localized at Xp21.1, accounts for 70% of XLRP in different populations. The RPGR (Retinitis Pigmentosa GTPase Regulator) gene that was isolated from the RP3 region is mutated in 20% of North American families with XLRP. From mutation analysis of 27 independent XLRP families, we have identified five novel RPGR mutations in 5 of the families (160delA, 789 A>T, IVS8+1 G>C, 1147insT and 1366 G>A). One of these mutations was detected in a family from Chile.